BEĞAVÎ'NİN MEÂLİMÜ'T-TENZÎL İSİMLİ TEFSİRİNDEKİ HADİSLERİN TAHRÎC VE DEĞERLENDİRİLMESİ (TEVBE SÛRESİ) - BULUT, GÜLZEMİN (Fırat Üniveristesi, 2018)
Çok yönlü ilmi kişiliği ile bilinen Beğavî'nin Meâlimu't-Tenzîl adlı eseri rivâyet türü tefsirleri arasında önemli bir yere sahiptir. Biz bu çalışmamızda Beğavî'nin hayatı, naklettiği rivayetler özelinde hocaları, talebeleri ve eserleri hakkında kısa bir bilgi verdikten sonra isnadlı ya da isnadsız çokça rivâyet barındıran Meâlimu't-Tenzîl'de Tevbe sûresinin tefsirinde kullandığı 116 rivâyetin tahrîcini ve değerlendirilmesini yapıp rivâyetlerin sıhhat değerlendirmesinde bulunduk. Rivâyetlerin değerlendirilme aşamasında Tirmizî, Şuayb el Arnavûd, Hâkim en-Neysâbûrî, Abdurrezzâk el-Mehdî, Abdulmuhsîn et-Türkî, Ahmed Muhammed Şâkir, Hüseyin Selim Esedü'd-Dârânî, Muhammed Fuad Abdulbâkî, Muhammed Avvâme, Elbânî, Fevvâz Ahmed ez-Zümerlî, Muhammed Kâmil Karabelli gibi muhaddis ve muhakkiklerin sıhhat değerlendirmelerinden istifadeyle görüş beyanında bulunduk. Kur'an ayetlerinin tefsiri sadedinde kullanılan bu 116 rivâyetin 63'ü sahîh, 9'u hasen, 36'sı zayıf, 5'i mevzûdur. Rivâyetlerin 3'ü hakkında da herhangi bir değerlendirmede bulunulmamıştır. Beğavî'nin tefsirinde kullandığı 116 rivâyetin yarısından fazlası yani 73'ü (%62,39) makbûl hadislerden oluşuyorken geriye kalan 41 (%35,04) rivâyetin 36'sı (%87,80) zayıf, 5'i (%12,19) de mevzû' nakillerdir. Bahsi geçen 116 rivâyetin 83'ü (% 70.94) Kütüb-i Tis'a'da, 7'si (% 5.98 ) diğer hadis kitaplarında, 24'ü (% 20.51 ) hadis kitapları dışında (Tefsir-Tarih vb.) yer alırken 2'si (% 1.70) başvurulan kaynaklarda tespit edilememiştir.

Al-Baghawi's Maalim at-Tanzil occupies an important place among the riwayah (narrative reports) method using tafasir(interpretations) whose author is famous for his interdisciplinary personality. In this study, we aim; after giving brief information about Al-Baghawi's life, teachers, disciples and works; to infer, analyze and evaluate the authenticity of 116 narratives in the part of surah At-Tawbah in Maalim At-Tanzil which contains quite a bit of narratives with and without reference. While evaluating the narratives we have benefited from the views of the muhaddithat (scholars of hadith) and researchers like; at-Tirmidhi, Shuaibal-Arna'ut, al-Hâkim at-Nishapuri, Abdul Razzaq al-Mahdi, Abdulmohsen at-Turki, Ahmad Muhammad Shakir, Hussein Saleem Asad Durrani, Muhammad Fuad Abdul Baqi, Muhammad Awwamah, Muhammad Nasiruddin al-Albani, Fawwaz Ahmad Zamarli and Muhammad Kamil Karabelli. Among these 116 narratives that were used to interpret the verses; we have evaluated them as 63 sound (saheeh), 9 good (hasan), 36 weak (da'if), 5 fabricated (mawdu). And 3 narratives were not adjudicated. In the interpretation (tafseer) of the muhaddith; 73(%62,39) narratives are acceptable (maqbul) which is more than half of the 116 narratives and 41(%35,04) of the narratives are rejected (mardud).Furthermore, among the rejected narratives, 36 out of 41 are weak and 5 are fabricated. In the 116 mentioned narratives; 83(%87.80) of them were found in the Nine Books of Hadith (al Kutub at-Tis'ah), 7 (%5.98) of them were in other hadith books, 24 (%20.51) were found in the non-hadith books (History, Tafseer etc.) and 2 (%1.70) could not be found in any source we have investigated.
The extraction and evaluation of hadiths in the commentary of al-Baghawi titled maalim at-tanzil (Surah at-tawbah)
Keywords: Din